Mortality risk remains higher in individuals with type 1 diabetes: A population‐based cohort study (the Ayrshire diabetes follow‐up cohort [ADOC]). Issue 8 (29th May 2018) - Collier, Andrew; Connelly, Paul J.; Hair, Mario; Cameron, Lyall; Ghosh, Sujoy; Waugh, Norman
Abstract : Aims: Type 1 diabetes is associated with an increased risk of cardiovascular disease and all‐cause mortality. Numerous studies have demonstrated that outcomes for diabetes are improved by intensive glycaemic control, blood pressure control, and treatment of dyslipidaemia in addition to cessation of smoking. The aim of this study was to compare mortalities in individuals with type 1 diabetes with that in non‐diabetic individuals, and to investigate the effects of age, gender, glycaemic control, socio‐economic status, hypertension, ischaemic heart disease (IHD), smoking status, body mass index (BMI) and dyslipidaemia. Methods: A population‐based analysis in Ayrshire and Arran, Scotland included 253 304 non‐diabetic individuals and 1324 individuals with type 1 diabetes who were tracked from 2009 to 2014. Results: Patients with type 1 diabetes had higher mortality rates than non‐diabetic individuals (HR, 3.20; P < .01), with relative mortality in female individuals with type 1 diabetes being higher than that in males (OR, 2.38 vs 1.52; P < .01). Increasing age (HR, 2.37), smoking (HR, 1.85), IHD (HR, 1.62) and hypertension (HR, 1.21) (all P < .01) increased mortality risk. A hypertensive female with type 1 diabetes and IHD who smoked had an HR of 11.6 compared with a non‐smoking, normotensive non‐diabetic female without IHD. For a hypertensive male with type 1 diabetes and IHD who smoked, HR was 6.96. BMI > 30 kg/m 2 was associated with reduced mortality risk in both non‐diabetic (HR, 0.61) and diabetic subjects (HR, 0.40). Conclusions: This study confirmed that the risk of mortality in individuals with type 1 diabetes remains elevated. Further studies are required to understand how gender affects the disparity in mortality and why obesity appears to be protective.